Precision targeting of androgen receptor–ferroptosis crosstalk in prostate cancer: From mechanisms to therapeutic strategies - Dongfang Lv; Yankang Shi; Luan Kou; Denglu Zhang; Yanxia Guo; Shengtian Zhao (Pharmacological Research)
Ferroptosis, an iron-dependent form of regulated cell death characterized by lipid peroxidation, has emerged as a promising vulnerability in cancer therapy. In prostate cancer (PCa), androgen receptor (AR) signaling remains a central oncogenic driver, with androgen deprivation therapy (ADT) as the standard of care. Emerging evidence suggests a bidirectional interaction between ferroptosis and AR signaling: ADT may sensitize cancer cells to ferroptosis by disrupting iron and lipid homeostasis, while ferroptosis-induced oxidative stress may in turn attenuate AR transcriptional activity. This review synthesizes current mechanistic insights into this interplay, highlighting key AR-regulated mediators of ferroptosis resistance, including MBOAT2, SLC7A11, and PEX10. We also discuss the therapeutic potential of dual-function agents, such as darolutamide and erastin, which simultaneously inhibit AR activity and induce ferroptosis, representing a novel strategy for treating castration-resistant prostate cancer (CRPC). Finally, we propose that combining ferroptosis inducers with AR-targeted therapies, guided by metabolic and redox biomarkers, may overcome therapeutic resistance and enable precision oncology approaches for advanced PCa.